Comment: The Next Frontier: Prosody Research Gets Interpersonal. (January 2021) - Pell, Marc D.; Kotz, Sonja A.
Neurocognitive models (e.g., Schirmer & Kotz, 2006) have helped to characterize how listeners incrementally derive meaning from vocal expressions of emotion in spoken language, what neural mechanisms are involved at different processing stages, and their relative time course. But how can these insights be applied to communicative situations in which prosody serves a predominantly interpersonal function? This comment examines recent data highlighting the dynamic interplay of prosody and language, when vocal attributes serve the sociopragmatic goals of the speaker or reveal interpersonal information that listeners use to construct a mental representation of what is being communicated. Our comment serves as a beacon to researchers interested in how the neurocognitive system "makes sense" of socioemotive aspects of prosody.